How to View the Parthenon through the Camera Obscura of the Tortoise. Issue 2 (8th September 2017) - Shaw, Wendy
Abstract : Visiting ruins, I enjoy the texture of the weathered stones. The wide space, colored in spring by wildflowers. Open space and vistas, the heady smell of grasses drying in the hot sun. Birds sing as they have since Plato's cicadas. Once, alone near the ruins, I heard a strange rhythmic clicking in the grass: two tortoises making love. The ruins that I visit remind me of antiquity not because I picture Socrates walking through the Stoa, but because I picture him walking along the still undeveloped riverbank, smelling these grasses, listening to these birds. The simplicity that I long for, however, is not millennia away, but only centuries. It is almost at arms' length, but just out of view. What I find there is nature in a frame of culture. Like most tourists, I cannot transform the stones into the imaginary film of antiquity that the European brain of the nineteenth century, steeped in a classical education, projected onto them. Yet their vision was no more authentic than mine: in order to project the past onto stones, they had to erase the present.